Do genetic predictors of pain sensitivity associate with persistent widespread pain? - Thomson Wendy; Macfarlane Gary J; Nicholl Barbara I; Holliday Kate L; Davies Kelly A; McBeth John (SAGE Publishing, 2009)
Abstract Genetic risk factors for pain sensitivity may also play a role in susceptibility to chronic pain disorders, in which subjects have low pain thresholds. The aim of this study was to determine if proposed functional single nucleotide polymorphisms (SNPs) in the GTP cyclohydrolase (GCH1) and μ opioid receptor (OPRM1) genes previously associated with pain sensitivity affect susceptibility to chronic widespread pain (CWP). Pain data was collected using body manikins via questionnaire at three time-points over a four year period from subjects aged 25-65 in the North-West of England as part of a population based cohort study, EPIFUND. CWP was defined at each time point using standard criteria. Three SNPs forming a proposed "pain-protective" haplotype in GCH1 (rs10483639, rs3783641 and rs8007267) and two SNPs in OPRM1 (rs1777971 (A118G) and rs563649) were genotyped in cases with persistent CWP (CWP present at ≥2 time-points) and controls who were pain-free at all time-points. The expectation-maximisation algorithm was used to estimate haplotype frequencies. The frequency of the "pain-protective" (CAT - C allele of rs10483639, A allele of rs3783641 and T allele of rs8007267) haplotype was compared to the frequency of the other haplotypes between cases and controls using the χ2 test. Allele frequencies and carriage of the minor allele was compared between cases and controls using χ2 tests for the OPRM1 SNPs. The frequency of the proposed GCH1 "pain-protective" haplotype (CAT) did not significantly differ between cases and controls and no significant associations were observed between the OPRM1 SNPs and CWP. In conclusion, there was no evidence of association between proposed functional SNPs, previously reported to influence pain sensitivity, in GCH1 and OPRM1 with CWP. Further evidence of null association in large independent cohorts is required to truly exclude these SNPs as genetic risk factors for CWP.